KEHIDUPAN YAKUZA DALAM NOVEL ASAKUSA BAKUTO ICHIDAI KARYA JUNICHI SAGA SEBUAH TINJAUAN SOSIOLOGI SASTRA - Pramartha, Gede Yudi (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} This thesis entitled "Yakuza Life in Asakusa Bakuto Ichidai Novel by Junichi Saga, A Review of Sociology Literature". This thesis analyzes yakuza life in the novel and it’s comparison with the yakuza life in Japan. Analysis of the sociology literature in the novel divided into three aspects. There are social aspect, cultural aspect and economic aspect. The results of social aspect analysis are about the oyabun-kobun relationship, senpai-kouhai relationship, kyoudai relationship, tradition of irezumi, tradition of yubitsume, and romantic aspect. The results of cultural aspect analysis explained ojigi’s culture in organization of yakuza. The results of economic aspect analysis explained gambling and drugs business of yakuza. The results of a comparison analysis of yakuza life in the novel with yakuza life in Japan explained that most of the yakuza life in Asakusa Bakuto Ichidai novel is a reflection of real life yakuza in Japan. Reflection on the Japanese yakuza life depicted in the novel can be seen from the Japanese yakuza organization principles, values bushidou, giri-ninjou, oyabun-kobun relationship management structure of yakuza organization, demukai tradition, irezumi tradition, yubitsume tradition, and business organization of yakuza in Japan. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: This thesis entitled " Yakuza Life in Asakusa Bakuto Ichidai Novel by Junichi Saga, A Review of Sociology Literature" . This thesis analyzes yakuza life in the novel and it’s comparison with the yakuza life in Japan. Analysis of the sociology literature in